The course of symptoms of anxiety and depression from time of diagnosis up to 2 years follow-up in head and neck cancer patients treated with primary (chemo)radiation. (March 2020) - van Beek, F.E.; Jansen, F.; Mak, L.; Lissenberg-Witte, B.I.; Buter, J.; Vergeer, M.R.; Voortman, J.; Cuijpers, P.; Leemans, C.R.; Verdonck-de Leeuw, I.M.
Highlights: Symptoms of anxiety and depression are common in HNC patients. HNC symptoms and HRQOL were associated with the course of anxiety and depression. Findings of this study support the need of tailored care in HNC patients. Abstract: Objectives: To identify sociodemographic and clinical factors, health-related quality of life (HRQOL) and head and neck cancer (HNC) symptoms associated with the course of symptoms of anxiety and depression from pretreatment to 24-month follow-up among HNC patients after (chemo)radiation. Materials and methods: Patients (n = 345) completed questionnaires on anxiety and depression (HADS), HRQOL and symptoms (EORTC QLQ-C30/QLQ-H&N35) before treatment, and 6-weeks, 3-, 6-12-, 18-, and 24-months after treatment. Mixed model analyses were used to investigate the course of anxiety and depression from pretreatment to 24-months in relation to factors assessed at baseline, and the course of anxiety and depression from 6- to 24-months, in relation to factors assessed at 6-months. Results: Increased risk for anxiety (HADS-anxiety > 7) was 28.7% among patients before treatment, which declined to 10.0% at 24-months. Increased risk for depression (HADS-depression > 7) was 15.1% before treatment, 18.2% at 3-months, 7.2% at 12-months and 16.0% at 24-months. Factors assessed at baseline which were significantly associated with the course of anxiety were age, pain, problems with social contact, and feeling ill, whereas chemotherapy, worse emotional functioning, speech problems and weight loss were significantly associated with the course of depression. Regarding factors assessed at 6-months, chemotherapy, worse cognitive and social functioning, insomnia, swallowing problems and trouble with social eating were associated with the course of anxiety. Nausea/vomiting, dyspnea, coughing, and feeling ill were associated with the course of depression (p-values < 0.05). Discussion: Factors associated with a worse course of anxiety and depression are younger age, treatment with chemotherapy, worse HRQOL and higher symptom burden.